2017
DOI: 10.4162/nrp.2017.11.4.300
|View full text |Cite
|
Sign up to set email alerts
|

Validation of dietary reference intake equations for estimating energy requirements in Korean adults by using the doubly labeled water method

Abstract: BACKGROUND/OBJECTIVESThe doubly labeled water (DLW) method is considered the gold standard for the measurement of total energy expenditure (TEE), which serves to estimate energy requirements. This study evaluated the accuracy of predictive dietary reference intake (DRI) equations for determining the estimated energy requirements (EER) of Korean adults by using the DLW as a reference method. SUBJECTS/METHODS Seventy-one participants (35 men and 36 women) aged between 20 and 49 years were included in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…Another study by Lee and Kim [ 32 ], which involved 28 male police officers aged 23 to 46 yrs (BMI = 24.6 ± 3.0), reported that the REE measured by indirect calorimetry was 1,748.3 ± 205.9 kcal/day. Our results are also comparable to those obtained by Kim et al [ 29 ], in a study that included 35 men aged 33.5 ± 8.8 yrs (BMI = 23.2 ± 2.1) and 36 women aged 33.3 ± 8.5 yrs (BMI = 22.2 ± 3.2). In that study, the measured REE was 1,695.3 ± 118.2 in men and 1,375.3 ± 160.1 in women.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Another study by Lee and Kim [ 32 ], which involved 28 male police officers aged 23 to 46 yrs (BMI = 24.6 ± 3.0), reported that the REE measured by indirect calorimetry was 1,748.3 ± 205.9 kcal/day. Our results are also comparable to those obtained by Kim et al [ 29 ], in a study that included 35 men aged 33.5 ± 8.8 yrs (BMI = 23.2 ± 2.1) and 36 women aged 33.3 ± 8.5 yrs (BMI = 22.2 ± 3.2). In that study, the measured REE was 1,695.3 ± 118.2 in men and 1,375.3 ± 160.1 in women.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, and in support of the results in previous studies [ 28 29 ], the measured REE was higher in men than in women; 1,793 ± 266 kcal/day and 1,368 ± 179 kcal/day, respectively ( P < 0.05). This difference can be explained by the observation that men in our study had significantly higher body weight and higher FFM than those in women, two factors that have previously been shown to positively correlate with an individual's REE [ 3 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, 68% of men and 64% of women showed TEE DRI values within 10% of the TEE DLW . In another study conducted by Kim et al [ 34 ], the accuracy of the DRI equation was assessed in 71 Korean adults (35 men and 36 women) aged between 20–49 years. According to the study findings, the DRI equation was accurate in this group with a bias of −1.3% in men and −4.9 in women as well as an accuracy rate of 77.1% in men and 62.9% in women.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study carried out with the elderly, this equation had a bias of -7.2% in men and − 6.6% in women [46]. Other study she was reported as accurate to estimate REE in men and women [47,48].…”
Section: Discussionmentioning
confidence: 98%